Fermentation Biotechnology Applied to Cereal Industry By-Products: Nutritional and Functional Insights - Verni, Michela; Rizzello, Carlo Giuseppe; Coda, Rossana (Frontiers in Nutrition, 2019)
Cereals are one of the major food sources in human diet and a large quantity of by-products is generated throughout their processing chain. These by-products mostly consist of the germ and outer layers (bran), deriving from dry and wet milling of grains, brewers’ spent grain originating from brewing industry, or others originating during bread-making and starch production. Cereal industry by-products are rich in nutrients, but still they end up as feed, fuel, substrates for biorefinery, or waste. The above uses, however, only provide a partial recycle. Although cereal processing industry side streams can potentially provide essential compounds for the diet, their use in food production is limited by their challenging technological properties. For this reason, the development of innovative biotechnologies is essential to upgrade these by-products, potentially leading to the design of novel and commercially competitive functional foods. Fermentation has been proven as a very feasible option to enhance the technological, sensory, and especially nutritional and functional features of the cereal industry by-products. Through the increase of minerals, phenolics and vitamins bioavailability, proteins digestibility, and the degradation of antinutritional compounds as phytic acid, fermentation can lead to improved nutritional quality of the matrix. In some cases, more compelling benefits have been discovered, such as the synthesis of bioactive compounds acting as antimicrobial, antitumoral, antioxidant agents. When used for baked-goods manufacturing, fermented cereal by-products have enhanced their nutritional profile. The key factor of a successful use of cereal by-products in food applications is the use of a proper bioprocessing technology, including fermentation with selected starters. In the journey toward a more efficient food chain, biotechnological approaches for the valorization of agricultural side streams can be considered a very valuable help.